Molecular patterns of oxidative stress in drug-induced nephropathy - Valentina Vitalyevna Lee; Larissa Evgenievna Muravlyova; Ryszhan Yemelevna Bakirova; Ahmet Kiziltunc; Zhanara Zholtaevna Turkhanova; Bolatkyl Dguzbaevna Ashirbekova (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Drug induced kidney disorder is a frequent adverse event which contributes to morbidity and even incapacitation. The discovery and development of novel biomarkers and local (renal) response mechanisms, are needed for effective prevention of drug-induced nephrotoxicity. Objectives: The main purpose of our study was to investigate the oxidative modifications of proteins in blood plasma and erythrocytes of patients with drug-induced nephropathies. Patients and Methods: Around105 patients were divided into two groups: first group was represented by patients with psychotropic drug-induced nephropathy; the second one consisted of patients received nonsteroidal anti-inflammatory drugs (NSAIDs). Advanced oxidation protein products (AOPPs) were measured by Witko-Sarsat method. Protein reactive carbonyl derivatives (PRCD) were assayed in blood plasma and erythrocytes by the Levine method. Neutrophil gelatinaseassociated lipocalin (NGAL) was determined with the use of a commercially available ELISA kit. Results: Carbonyl derivatives are significantly higher in red blood cells of the 1st and 2nd group patients compared to the control subjects. AOPP statistically increased both in patients with various types of drug nephropathy and in patients with chronic kidney disease (CKD) compared with the control group. The NGAL was significantly higher in all groups compared to the control subjects. Conclusion: The patients with drug-induced nephropathy have increased level of oxidative stress products and response NGAL reaction. The mechanisms that lead to the development of oxidative stress and the production of modified proteins are different in patients treated with different drugs. Establishing patterns of cell-molecular interaction permit the drug-induced nephropathy to be timely diagnosed and therapeutic programs to be optimized.